Coordinating irrigation and nitrogen fertilization with precipitation maximizes yield and economic traits in winter wheat (Triticum aestivum L.) - Juan Kang; Geng Ma; Weixing Liu; Hongfang Lu; Yingying Chu; Guangxin Ru; Yingxin Xie; Dongyun Ma; Chenyang Wang (Journal of Agriculture and Food Research)
With increasingly frequent climate extremes and serious environmental pollution, it is important to study the effects of irrigation and nitrogen (N) application on wheat production and resource conservation in dry, normal, and wet precipitation year types. A 6-year field experiment with three irrigation levels (W0, no irrigation; W1, irrigation at jointing; W2, irrigation at jointing and flowering) and four N rates (N0, 0; N180, 180 kg hm−2; N240, 240 kg hm−2; N300, 300 kg hm−2) was established at three sites in the North China Plain (NCP). The results showed that irrigation, N rate, and rainfall had significant effects on yield, water use efficiency (WUE), partial factor productivity of N (NUEp), and economic benefit (EB). A N application rate of 180 kg hm−2 achieved high NUEp. Applying two irrigations in dry/wet years and one in normal years balanced high yield with EB. Response surface methodology analysis based on binary quadratic regression showed that yield, EB, and NUEp could be balanced (>95 % of maximum values) when water consumption was within a range of 423–495, 371−415, and 535−600 mm, and N rates were within a range of 126–200, 167−172, and 146−193 kg hm−2, for dry, normal, and wet years, respectively. In summary, optimizing N application and irrigation management according to variation in annual precipitation can simultaneously balance yield and economic traits, promote the sustainable development of resources, and protect the environment in the NCP.